Towards a remote portable bio-affinity surface plasmon resonance analyser for environmental steroidal-pollutants - Sesay, Adama Marie (Cranfield University, 2003)
The widespread presence of chemicals with the capacity to disrupt the endocrine system in both wildlife and humans in our natural environment has increasingly become of major concern in the last ten years. Endocrine disrupting compounds (EDCs) are a group of compounds that pose a potentially dangerous and real threat to the health of both humans and wildlife. These substances can mimic or interfere with the biological pathways of natural endogenous signalling chemicals controlling the endocrine system (e.g. sex hormones). Endocrine disrupters are ubiquitous in water. The detection, monitoring and treatment of wastewaters and surface waters for EDCs would significantly help minimise the environmental burden imposed by these natural and synthetic compounds. To optimise such processes, an economical, in-situ or field-based detection technique for EDCs is required. The research presented in this thesis describes the development of a portable surface plasmon resonance device for the detection of endocrine disrupters in wastewater and surface waters. The first two result chapters describe the construction, development and optimisation of the portable analyser and immunoassay protocol using anti-estrogenic antibodies. A novel approach for regenerating the SPR sensing surface was achieved by using Persil biological laundry liquid (1%). The developed immunoassay showed a working range between 0.2 - 7µg/L for Estrone-3-Gulcuronide (E13G) in buffer. The detection of 17beta- Estradiol (E2) in buffer, synthetic wastewater and real wastewater samples was also carried out; the working range was 0.1 - 10µg/L; 0.3-7µg/L and 0.1-10µg/L respectively. The second part of the thesis describes the synthesis and protocol development of a photo-chromic dye and its application to immuno-sensing systems en route to a reversible bio-affinity antibody for application to regenerating biosensing surfaces. This approach was to demonstrate the concept of remote regeneration of the active sensing surface for a portable optical sensor.